Investing for dummies - Tyson, Eric (Eric Kevin) (Hoboken, NJ : John Wiley & Sons, Inc., 2014)
Invest in your financial future with this valuable, popular, and easy-to-use guide This latest edition is infused with new and updated material to help you ramp up your portfolio today! This includes time-tested advice, updates to investing recommendations, and strategies that reflect changing market conditions. Investing may be an intimidating prospect, but this resource will serve as your primer on all aspects of the topic, including how to develop and manage a portfolio, invest in stocks, bonds, mutual funds, and real estate, open a small business, and more.
Part I: Investing fundamentals. Exploring your investment choices ; Weighing risks and returns ; Getting your financial house in order before you invest -- Part II: Stocks, bonds, and Wall Street. The workings of stock and bond markets ; Building wealth with stocks ; Investigating and purchasing individual stocks ; Exploring bonds and other lending investments ; Mastering mutual funds and exchange-traded funds ; Choosing a brokerage firm -- Part III: Growing wealth with real estate. Investing in a home ; Investing in real estate ; Real estate financing and deal making -- Part IV: Savoring small business. Assessing your appetite for small business ; Starting and running a small business ; Purchasing a small business -- Part V: Investing resources. Selecting investing resources wisely ; Perusing periodicals, radio, and television ; Selecting the best investment books ; Investigating internet and software resources -- Part VI: The part of tens. Ten investing obstacles to conquer ; Ten things to consider when weighing an investment sale ; Ten tips for investing in a down market.
Includes index.(3SjO GdJhfSj (B/ (3cJH cdjI GdGbJUGO hGdGOGQIs
Keywords: Finance, Personal; Finance; Investments